The Public/Private Dynamics in Polish Higher Education. Demand-Absorbing Private Sector Growth and Its Implications - Kwiek, Marek (My University, 2012)
The paper links several interrelated processes in Central and Eastern European higher education: expansion through two types of privatization (external: new private providers, and internal, public universities charging fees in a nominally free public sector), severe fiscal constraints limiting further tax-based growth of higher education, and the gradual denigration of the research mission of universities caused by almost two decades of their continuous focus on the teaching mission and by general underfunding of university research in the region. Long-term consequences of the unprecedented growth of the private sector in Poland in the two decades of 1990-2010 are studied, with special emphasis on the consequences of accompanying processes of the deinstitutionalization of the university research mission taking place in public universities: the decreasing role of traditional academic institutional rules and norms and traditional institutional patterns of academic behavior in Polish universities in the period. A new wave of reforms in Poland (2008-2011) is discussed, as possibly leading to substantially revised rules, norms and patterns of institutional behavior. Poland, with 31.5% of student enrollments in the private sector in 2010 (out of 1.84 million students), provides a unique case to study the two decades of demand-absorbing growth of private higher education with all its advantages and, as mostly discussed in the present chapter, limitations. The overall context of the chapter is the emphasis on further expansion of higher education in Europe argued for by both knowledge economy theories and (repeatedly) by the European Commission policy documents, with a policy wish to close the enrollment gap between the European Union and the USA. Finally, the chapter presents conclusions and directions for further research. Experimenting with privatization in higher education, substantially increasing access to it in the last ten to fifteen years, were especially strong in Central European systems, Poland being the biggest system in the region and the most notable example. New “public-private dynamics” (Enders and Jongbloed 2007), in various forms, emerges in Europe and the chapter focuses on those systems which have used privatization processes for the expansion of their higher education in the context of increasingly competitive public funding for all public services generally, not only for higher education. Especially, the chapter studies the long-term consequences of the expansion through privatization for the system as a whole and for public sector institutions.
Keywords: public-private dynamics; private higher education; private universities; Poland; Polish reforms; educational reforms; Central Europe; educational expansion; privatization; internal privatization; external privatization; Daniel C. Levy; expanding higher education; independent private higher education; fee-paying; cost-sharing; global scripts; isomorphism; isomorphic change; deinstitutionalization; research mission; reinstitutionalization; denigration of the research mission; academic norms; academic rules; decline in research; hard and soft fields; institutionalism; normative institutionalism